Development of Portuguese as a second language for deaf people at university: a didactic proposal for reading academic abstracts - Fagundes, Isabelle Pinheiro; Reinaldo, Maria Augusta Gonçalves de Macedo (The ESPecialist, 2024)
The growing interest in written language has captured the attention of researchers engaged in the study of deafness, prompting a series of inquiries into the essential strategies and approaches to promote the development of reading and writing skills in deaf students. This article aims to analyze the results of teaching activities focused on Portuguese language centered on the academic abstract genre, developed for and with deaf students from the Libras Letters course at a public university in the northern interior of Rio Grande do Norte. The analyzed activities are part of the first phase of a didactic sequence (DOLZ, NOVERRAZ; SCHNEUWLY, 2004), linked to an ongoing doctoral research project. The results show that the activities carried out were successful, as they allowed students to express their thoughts in writing on the topic discussed, using sign language as a basis for their writing process. Through these activities, we were able to promote contact with written materials in the academic environment, encouraging reading and writing without suppressing Portuguese language in favor of Libras.